Simulasi CFD Gasifikasi Pada TWO Stage Gasifier Tipe Venturi Klasik Dengan Bahan Baku Tandan Kosong Sawit - Mitrodono H L Gaol; Romy Romy; Zulfansyah Zulfansyah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Biomass gasification is a very complex thermo chemical process which involves the reaction of a chemical reaction. The purpose of this study was to determine the reactor dimensions as a reference in making a gaifier made from empty fruit bunches by obtain optimum working conditions and simulate CH4, CO, dan H2 pruducts in the reactor by varying the amount and position of air entering the reactor. This researh utilized software GAMBIT 2.4.6 for meshing and boundary identification and FLUENT 6.3.26 for simulation. Mass flow rate of feed empty fruit bunches waste in the simulation was 10 kg/jam with variations of air equivalence ratio ie 0.2, 0.25, 0.3 and the number of nozzles 2,3 and 4. From the simulations results, the highest combustible gas was obtained when the variable of ER value = 0.3 and number of nozel 2 ie CO = 18.53 %, H2 = 0.9 % and CH4 = 0.0365 % with HHV = 24.85 kJ/Nm3.Keywords : Empty Palm Bunches, Gasification, CFD, FLUENT